Design and fabrication of a hybrid DC voltage regulator with a novel isolation circuit - Kumar S.; Srivastava R.K. (My University, 2025)
Industrial and residential appliances which use DC power often require regulated power supply. If the input supply is DC, then the usual way is to use Pulse Width Modulated (PWM) DC-DC converters. This paper presents a hybrid regulator which has been designed especially for a Brushless DC fan requiring very robust control on the input voltage. The hybrid regulator requires a novel isolation circuit which energizes the control circuits. The overall aim is to build a cheap, simple and better alternative to PWM based DC-DC converters. Performance comparison of the hybrid regulator and conventional PWM based DC-DC buck-boost regulator has been investigated using MATLAB SIMULINK. The test results have also been discussed. © 2014 IEEE.